2003
DOI: 10.1063/1.1620994
|View full text |Cite
|
Sign up to set email alerts
|

Are both symmetric and buckled dimers on Si(100) minima? Density functional and multireference perturbation theory calculations

Abstract: We report a spin-unrestricted density functional theory(DFT) solution at the symmetric dimer structure for cluster models of Si(100). With this solution, it is shown that the symmetric structure is a minimum on the DFTpotential energy surface, although higher in energy than the buckled structure. In restricted DFT calculations the symmetric structure is a saddle point connecting the two buckled minima. To further assess the effects of electron correlation on the relative energies of symmetric versus buckled di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 50 publications
1
35
1
Order By: Relevance
“…Our earlier study of the silicon dimers found the UB3LYP solution to indeed exist and be lower in energy than the B3LYP solution, the spinunrestricted solution was, therefore, preferred in a variational sense. 25 However, in the present study we find that using spin-restricted Kohn-Sham orbitals yields a lower XYGJ-OS energy when additionally considering the perturbative correlation effects. The same behavior was observed for other DHDFs considered here.…”
Section: Doubly Hybrid Density Functional Calculationscontrasting
confidence: 40%
See 3 more Smart Citations
“…Our earlier study of the silicon dimers found the UB3LYP solution to indeed exist and be lower in energy than the B3LYP solution, the spinunrestricted solution was, therefore, preferred in a variational sense. 25 However, in the present study we find that using spin-restricted Kohn-Sham orbitals yields a lower XYGJ-OS energy when additionally considering the perturbative correlation effects. The same behavior was observed for other DHDFs considered here.…”
Section: Doubly Hybrid Density Functional Calculationscontrasting
confidence: 40%
“…Interestingly, a similar trend was observed in the DFT calculations for two, three, and four dimers. 25 The CASPT2 calculations show an opposite trend. We also note that the MRCI (+Q) calculations on (U)B3LYP geometries yield almost same results, showing a weak geometry dependence between (U)B3LYP and XYGJ-OS in the present case.…”
Section: Wave Function Based Calculations (Single-and Multi-refementioning
confidence: 91%
See 2 more Smart Citations
“…While clearly needed for dissociation, there are also some cases where it is known that significantly different stable structures can be obtained in DFT when spin-polarization is allowed. 24 …”
Section: Orbital Stability and Spin-polarization In Density Functionamentioning
confidence: 99%